Namen im südlichen Ermland. Beobachtungen zur Tätigkeit von Komisja Ustalania Nazw Miejscowości am Beispiel von Toponymen der Gemeinden Gietrzwałd und Stawiguda - Lobert, Magdalena Lidia (2023)
In the article, selected names of places in southern Warmia will be discussed and subjected to linguistic analysis. On this basis, the division of these toponyms will be made in terms of the linguistic affiliation of their morphemes, which have their source in Polish, German and Prussian. The history of the activity of the Commission for the Determination of Place Names will also be presented, which after World War II, immediately after the incorporation of Warmia into the Polish state, began intensive work on giving German names their Polish equivalents. The collected material will make it possible to formulate the methods most likely used by the Commission during its work, as well as to show conclusions regarding the impact of national identity and state policy on changes in the naming of places in Warmia.
Keywords: Onomastics; Toponomastics; Polish toponyms; German toponyms; Repolonization; Hybrid names